Optimasi Antarmuka dan Pengalaman Pengguna pada Website Promosi Pondok Pesantren Al-Murtadlo Ponjong dengan Metode Design Thinking - Lukman Hakim Aljihadu; Nur Widjiyati (Pengelola Jurnal Politeknik Negeri Ketapang, 2026)
Al-Murtadlo Islamic Boarding School Ponjong does not yet have a digital promotional medium. Information about the Islamic boarding school is still limited to direct communication, resulting in a lack of public awareness regarding its profile, students’ achievements, activities, and overall strengths. This study aims to design a user interface and user experience (UI/UX) for the Pondok Pesantren Al-Murtadlo Ponjong website. The design thinking method is applied as the research approach. The research process consists of five stages: empathize, define, ideate, prototype, and testing. The design evaluation is conducted using the User Experience Questionnaire (UEQ). The outcome of this study is a UI/UX prototype featuring profile, program, instructors, achievements, gallery, contact, and admin dashboard features. The usability testing results indicate that the design achieved Excellent and Good categories.